2000
DOI: 10.1074/jbc.m002160200
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Protein Kinase Cε in the Inhibitory Effect of Epidermal Growth Factor on Calcium-stimulated Chloride Secretion in Human Colonic Epithelial Cells

Abstract: Epidermal growth factor (EGF) inhibits carbachol-induced chloride secretion in T 84 colonic epithelial cells and has been shown to activate phosphatidylinositol (PI) 3-kinase, leading to inhibition of a basolateral potassium conductance. We asked whether the inhibitory effect of EGF on secretion is due to activation of specific isoforms of protein kinase C (PKC) by PI 3-kinase. Western analysis revealed that PKC␣, ␥, ⑀, , , /, and were expressed in T 84 cells. Ro318220 (an inhibitor active against PKC⑀, 10 M) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 36 publications
(45 reference statements)
6
45
1
Order By: Relevance
“…Thus, in our study, the inhibitory effect of wortmannin on PMA-induced activation of PKC⑀ favors an essential role of the second messengers of PI3-kinase pathway and suggests a downstream position of PKC⑀ related to PI3-kinase. Our data are also in accordance with the previous findings of Chow et al (10) showing that the ability of EGF to inhibit CCh-induced Cl Ϫ secretion in T84 cells was completely reversed by the PI3-kinase inhibitor wortmannin and that PKC⑀ acts as a downstream effector to PI3-kinase in T84 cells stimulated with EGF. Moreover, we have also shown the increased translocation of PKC⑀ from the cytosol to the membrane fractions in Caco-2 cells in the presence of the PI3-kinase activator IRS-1 peptide.…”
Section: /Ohsupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, in our study, the inhibitory effect of wortmannin on PMA-induced activation of PKC⑀ favors an essential role of the second messengers of PI3-kinase pathway and suggests a downstream position of PKC⑀ related to PI3-kinase. Our data are also in accordance with the previous findings of Chow et al (10) showing that the ability of EGF to inhibit CCh-induced Cl Ϫ secretion in T84 cells was completely reversed by the PI3-kinase inhibitor wortmannin and that PKC⑀ acts as a downstream effector to PI3-kinase in T84 cells stimulated with EGF. Moreover, we have also shown the increased translocation of PKC⑀ from the cytosol to the membrane fractions in Caco-2 cells in the presence of the PI3-kinase activator IRS-1 peptide.…”
Section: /Ohsupporting
confidence: 83%
“…PKC⑀, the isoform sensitive to RO-318220, was previously shown to lie downstream of PI3-kinase in signal transduction cascades in other systems (10). It was therefore of interest to determine whether PI3-kinase pathway is involved in the PMA-mediated inhibition of Cl Ϫ /OH Ϫ exchange process in Caco-2 cells.…”
Section: Effect Of Pi3-kinase Inhibitors Wortmannin and Ly-294002 On mentioning
confidence: 99%
“…One possibility is that PI3K may alter the activity of one or more of the transport proteins that comprise the Cl Ϫ secretory machinery, and in this regard PI3K has been shown to alter ion channel activity in some cell types (48,49). However, previous studies from our laboratory suggest an inhibitory effect of PI3K on intestinal epithelial K ϩ channels (50), an effect that does not explain our current data because inhibition of K ϩ channel function would likely lead to attenuation of Cl Ϫ secretory responses (2). It is also important to note, however, that these previous studies related to secretory responses elicited by Ca 2ϩ -dependent agonists and, perhaps, to a separate population of K ϩ channels to those involved in cAMP-mediated secretory responses.…”
Section: Discussioncontrasting
confidence: 43%
“…Although the biological roles of both PKCε and Lck have been extensively studied in a variety of systems (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(26)(27)(28)(29)(30)(31)(32)(33), it is unknown whether these two kinases interact and, if so, in which specific manner they interact, and whether their coordinated interactions are required to govern signal transduction during the genesis of a biological phenotype (such as protection against ischemic injury). In the present investigation, we found that PKCε interacted with, phosphorylated, and activated Lck; that is, PKCε and Lck functioned as a signaling module.…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of the intracellular signaling mechanisms by which cells protect themselves against ischemia-induced damage bears great clinical significance with respect to the treatment and prevention of tissue injury (1)(2)(3). The ε isoform of protein kinase C (PKCε) is a member of the PKC family of serine/threonine kinases and has been implicated in the protection against injury in multiple organ systems (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). In the heart, activation of PKCε has been shown to mediate the development of preconditioning (4,5,(11)(12)(13), a powerful cardioprotective adaptation that can be produced either by brief episodes of ischemia followed by reperfusion, or by the administration of pharmacological agents that can mimic the effects of ischemic preconditioning (1,(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%